(untitled) - Nayfeh, Ali Hasan (New Jersey, 1973)
Contents: straightforward expansions and sources of nonuniformity; the method of multiple scales; asympotic solutions of linear equations.
Keywords: Perturbation (Mathematics),Mở rộng tiệm cận,Sự nhiễu loạn (toán học),Differential equations,Phương trình vi phân,Asymptotic expansions